LIMITES E POSSIBILIDADES DAS APRENDIZAGENS COLABORATIVAS NO ENSINO DA LÍNGUA PORTUGUESA POR MEIO DO APLICATIVO WHATSAPP - OLIVEIRA, Jairo Belchior Freitas (2023)
The objective of this study is to analyze collaborative learning developed by Portuguese Language teachers, through the WhatsApp application, among 9th grade students in the public municipal school system of Marabá-PA. To this end, some steps were followed: we characterized the collaborative learning promoted by 9th grade Portuguese Language teachers in the public municipal school system of Marabá, from the planning stage, with emphasis on the use of the WhatsApp application; we described the main challenges faced by teachers in using this application as a teaching tool in collaborative learning among students; and we identified the relationships between the collaborative learning networks promoted by students, through the WhatsApp application, and the mediation of Portuguese Language teachers. This is an exploratory research of a qualitative nature, carried out in two phases: bibliographical survey and field research, with semi-structured interviews and document analysis being carried out in the last phase. From a theoretical perspective, we discussed authors who discuss the teaching of Portuguese, Digital Information and Communication Technologies (DICTs) in education and Digital Literacy. The participants in the research were four Portuguese teachers from the municipal school system in Marabá/PA who work in 9th grade classes. The data were organized into categories and the analysis followed the guidelines of the triangulation method. The results indicate the lack of access, as well as the issue of the quality of access to DICTs. The difficulty in individually assessing students in group activities was pointed out as one of the main difficulties in developing collaborative activities. It was also evident that, despite the numerous difficulties faced, the teachers demonstrated their commitment to learning, seeking new teaching strategies and developing collaborative activities using WhatsApp, whenever necessary. The data indicate the need to discuss the issue investigated in depth, as it is a current and fundamentally important topic, which helps us to increasingly understand the inclusion of new technologies in the school environment and the possibility of collaborative learning through the WhatsApp application.